Penentuan Harga Pokok Penjualan Metode Fullcosting dan Harga Jual Lengkuas di Desa Matanair Kabupaten Sumenep - Ramadani, Samsul Arif; Nurhayati, Citra (Journal of Economics and Management Scienties, 2024)
Farmers are generally not free to determine the selling price of their agricultural products, as it is the middlemen who set the purchase price. However, the selling price is a crucial factor in determining the sustainability of farming, especially in the cultivation of galangal in Matanair Village, Sumenep Regency. This research examines the determination of the full costing method for the cost of goods sold (COGS) and the selling price of galangal in Matanair Village, Sumenep Regency. The full costing method is employed to calculate the COGS, incorporating all production costs, both fixed and variable, and also the costs not considered by farmers, such as the labor of the farmers themselves, into the cost price. In calculating the COGS, the researcher analyzes each stage of galangal cultivation, starting from land preparation, planting, maintenance, to harvesting. Through interviews with galangal farmers, production cost data is obtained and calculated using the full costing method. The results of this study indicate that the COGS of galangal according to the full costing method differs from the calculations made by farmers. According to the full costing method, more than 80% is attributed to the harvesting stage. If identified based on cost accounting concepts, more than 90% of the total COGS is attributed to labor costs incurred by farmers. Therefore, this can be a focus for farmers in managing costs, particularly during the harvest season and in terms of labor costs.